Alginate oligosaccharides enhance the antifungal activity of nystatin against candidal biofilms - Powell, Lydia C.; Adams, Jennifer Y. M.; Quoraishi, Sadik; Py, Charlène; Oger, Anaϊs; Gazze, Salvatore A.; Francis, Lewis W.; von Ruhland, Christopher; Owens, David; Rye, Philip D.; Hill, Katja E.; Pritchard, Manon F.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The increasing prevalence of invasive fungal infections in immuno-compromised patients is a considerable cause of morbidity and mortality. With the rapid emergence of antifungal resistance and an inadequate pipeline of new therapies, novel treatment strategies are now urgently required. The antifungal activity of the alginate oligosaccharide OligoG in conjunction with nystatin was tested against a range of Candida spp. (C. albicans, C. glabrata, C. parapsilosis, C. auris, C. tropicalis and C. dubliniensis), in both planktonic and biofilm assays, to determine its potential clinical utility to enhance the treatment of candidal infections. Minimum inhibitory concentration (MIC) and growth curve assays demonstrated the synergistic effects of OligoG (0-6%) with nystatin, resulting in an up to 32-fold reduction in MIC, and a significant reduction in the growth of C. parapsilosis and C. auris (minimum significant difference = 0.2 and 0.12 respectively). Confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM) imaging demonstrated that the combination treatment of OligoG (4%) with nystatin (1 µg/ml) resulted in significant inhibition of candidal biofilm formation on glass and clinical grade silicone surfaces (p < 0.001), with increased cell death (p < 0.0001). The ATP biofilm disruption assay demonstrated a significant reduction in cell viability with OligoG (4%) alone and for the combined OligoG/nystatin (MIC) treatment (p < 0.04) for all Candida strains tested. Transmission electron microscopy (TEM) studies revealed the combined OligoG/nystatin treatment induced structural reorganization of the Candida cell membrane, with increased permeability when compared to the untreated control (p < 0.001). Antimicrobial synergy between OligoG and nystatin against Candida spp. highlights the potential utility of this combination therapy in the prevention and topical treatment of candidal biofilm infections, to overcome the inherent tolerance of biofilm structures to antifungal agents.